Quantitative cardiac CT perfusion: physiologically-inspired model and identifying microvascular disease from discordant CTA CAD-RADS - Wu, Hao; Song, Yingnan; Hoori, Ammar; Lee, Juhwan; Al-Kindi, Sadeer; Huang, Wei-Ming; Yun, Chun-Ho; Hung, Chung-Lieh; Rajagopalan, Sanjay; Wilson, David L. (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveUse our advanced, physiologically inspired cardiac CT perfusion (CCTP) software to distinguish ischemia due to obstructive disease vs. microvascular disease (MVD).BackgroundPreviously validated advanced CCTP methods were used. We interpreted results to identify flow-limiting stenosis [i.e., obstructive-lesion & low myocardial blood flow (MBF)] vs. microvascular disease (i.e., no-obstructive-lesion & low-MBF).MethodsWe retrospectively evaluated 104 patients with suspected CAD, including 18 with diabetes, who underwent CCTA + CCTP. Whole heart and territorial MBF was assessed using our automated pipeline for CCTP analysis that included beam hardening correction; temporal scan registration; automated segmentation; fast, accurate, robust MBF estimation; and visualization. Stenosis severity was scored using the CCTA coronary-artery-disease-reporting-and-data-system (CAD-RADS), with obstructive stenosis deemed as CAD-RADS ≥ 3.ResultsWe established a threshold MBF (MBF = 200-mL/min-100 g) for normal perfusion. In patients with CAD-RADS ≥ 3 (obstructive disease), 28/37(76%) patients showed ischemia in the corresponding territory. On a per-vessel basis (n = 256), MBF showed a significant difference between territories with and without obstructive stenosis (165 ± 61 mL/min−100 g vs. 274 ± 62 mL/min−100 g, p < 0.05). A significant negative rank correlation (ρ = −0.53, p < 0.05) between territory MBF and CAD-RADS was seen. Two patients with obstructive disease had normal perfusion, suggesting collaterals and/or hemodynamically insignificant stenosis. Among diabetics, 10 of 18 (56%) demonstrated diffuse ischemia consistent with MVD. Among non-diabetics, only 6% had MVD. Sex-specific prevalence of MVD was 21%/24% (M/F).ConclusionCCTA in conjunction with a new automated quantitative CCTP approach can determine the distinction of ischemia due to obstructive lesions vs. MVD.